Battle of ink and ice : a sensational story of news barons, North Pole explorers, and the making of modern media - Hartman, Darrell (Viking, 2023)
"A sixty-year saga of frostbite and fake news that follows the no-holds-barred battle between two legendary explorers to reach the North Pole, and the newspapers which stopped at nothing to get--and sell--the story. In the fall of 1909, a pair of bitter contests captured the world's attention. The American explorers Robert Peary and Frederick Cook both claimed to have discovered the North Pole, sparking a vicious feud that was unprecedented in international scientific and geographic circles. At the same time, the rivalry between two powerful New York City newspapers--the storied Herald and the ascendant Times--fanned the flames of the so-called polar controversy, as each paper financially and reputationally committed itself to an opposing explorer and fought desperately to defend him. The Herald was owned and edited by James Gordon Bennett, Jr., an eccentric playboy whose nose for news was matched only by his appetite for debauchery and champagne. The Times was published by Adolph Ochs, son of Jewish immigrants, who'd improbably rescued the paper from extinction and turned it into an emerging powerhouse. The battle between Cook and Peary would have enormous consequences for both newspapers, and help to determine the future of corporate media. Battle of Ink and Ice presents a frank portrayal of Arctic explorers, brave men who both inspired and divided the public. It also sketches a vivid portrait of the newspapers that funded, promoted, narrated, and often distorted their exploits. It recounts a sixty-year saga of frostbite and fake news, one that culminates with an unjustly overlooked chapter in the origin story of the modern New York Times. By turns tragic and absurd, Battle of Ink and Ice brims with contemporary relevance, touching as it does on themes of class, celebrity, the ever-quickening news cycle, and the benefits and pitfalls of an increasingly interconnected world. Above all, perhaps, its cast of characters testifies--colorfully and compellingly--to the ongoing role of personality and publicity in American cultural life as the Gilded Age gave way to the twentieth century--the American century"--